Unoccupied Aircraft Systems Sampling for Earth and Mars - Colin Chen; Christopher W. Hamilton; Christian Sipe; Kathryn Bywaters; Justin Lawrence; Paul Creekmore; Nicklaus Traeden; Kris Zacny (The Planetary Science Journal, 2025)
Unoccupied aircraft systems (UAS) technology on Earth has become increasingly prevalent and accessible, and for extraterrestrial applications, the Ingenuity helicopter has proven the viability of flight on Mars. Advantages provided by UAS on both Earth and Mars include faster and broader access to traditionally difficult-to-reach terrain. Here, we demonstrate the use of UAS-based sample collection and retrieval systems for applications on Earth and Mars, which we tested in Martian analog sites in the Holuhraun region of Iceland, at the Galena Creek rock glacier in Wyoming, and around the Eastern Sierra in California. The two sampling systems include a Drill Sampler and a Scoop Sampler, both coupled to commercial off-the-shelf drones. The Drill Sampler is a lightweight rotary-percussive coring drill with powder collection capability, compliantly mounted to the UAS to allow for drilling into a variety of different materials and uneven terrain. The Scoop Sampler uses modular interchangeable scoops for collecting and retrieving different types of samples. These sampling systems collected a suite of various samples, including rock cores, bulk samples, and replica Mars sample tubes. By collecting various samples in diverse terrains, we show that this technology enables adaptable sampling and sample transport for both earthbound and future planetary exploration missions.